Evaluación de tres distancias de siembra en estado fenológico vegetativo de plantas meristemáticas de banano en la granja santa inés - Vicente Castillo, Gema Briggitt (Machala : Universidad Técnica de Machala, 2021)
The cultivation of bananas and plantains is the twelfth in the ranking of production and the most important fruit for sale in the world; (Musa x paradisiaca) is one of the clones with the greatest presence in the production of the regions on the coast, reaching 89%; saw 10%, and orient 1%.; In most regions, Williams predominates, its sowing distance is very varied, depending on the area and soil characteristics, it is sown at 2.7 x 2.9 m between plants, an average of 1450 to 1500 plants per hectare; thus producing 2500 to 2800 boxes per year; in El Oro it is the most cultivated. The objective of this project was to evaluate the three sowing distances in the cultivation of musacea in the vegetative state of the crop, in the Santa Inés Farm of the Technical University of Machala; from the El Oro province, in order to evaluate its morphological characteristics according to the distance and its presence of chlorophyll in the plant. In the test area, a completely randomized block experimental design (BCA) was used, with different planting distances in the 6 plots with 20 repetitions, making a total of 60 plants to evaluate Treatment 1; Treatment 2; Treatment 3. The variables evaluated were: plant height; foliar emission; number of sheets; chlorophyll (third leaf); leaf area; The stem of the plant was placed with the same fertilization at different distances to see the effect. The analysis of the data was indicating that in its vegetative stage there is no statistical but numerical significance that is not influenced by the interaction of the sowing distance; the sowing methods did not affect the variables. Its foliar emission in its vegetative phase (1.2 weekly leaves) the distance with the greatest statistical change was Treatment 3 (1.3 leaves) with its highest mean compared to the other distances; the best result was obtained by reducing the sowing distance. At its height, Treatment 1 reached (46.34 cm) while Treatment 3 reached (46.27 cm) and Treatment 2 reached its means (46.24 cm) respectively. Regarding the variables of the number of leaves, Treatment 1 stands out, being the best result in leaves (12.50) while Treatment 2 reached its means (12.43) and Treatment 3 (12.36); the stem stands out Treatment 1 was the best result (2.03 cm); Regarding the foliar area, the result that stands out the most is Treatment 1 with a result (0.27 〖cm〗^2); its variable chlorophyll the third leaf was taken to see the greenness of the leaf the best treatment in the different distances is Treatment 1 obtained the best in chlorophyll (62.01 µ.〖cm〗^(-2)). Treatment 1 in the following variables had the best result; (Height) with a value of 46.34, number of leaves with a value of 12.50 leaves, stem with 2.03 cm, leaf area with a value of 0.27 〖cm〗^2 and chlorophyll with a value of (62.01 µ.〖cm〗^(-2)). In Treatment 1, planting distances do not influence the first stages in terms of the variables that we verify in the trial; Also to the human eye, the culture did not present major differences in the batches.
El cultivo de banano y plátano es el duodécimo en el ranking de producción y la fruta más importante de venta en el mundo; (Musa x paradisiaca) es de los clones con mayor presencia en la producción de las regiones en la costa alcanza un 89%; sierra un 10%, y oriente 1%.; en la mayoría de las regiones predomina el Williams su distancia de siembra es muy variada va a depender de la zona y características del suelo se siembra a 2.7 x 2.9 m entre plantas un promedio de 1450 a 1500 plantas por hectáreas; así produciendo 2500 a 2800 cajas por año; en El Oro es el más cultivado. El objetivo de este proyecto fue evaluar las tres distancias de siembra en el cultivo de musáceas en estado vegetativo del cultivo, en la Granja Santa Inés de la Universidad Técnica de Machala; de la provincia El Oro, con la finalidad de evaluar sus características morfológicas según el distanciamiento y su presencia de clorofila en la planta. En el área de ensayo se utilizó un diseño experimental de bloques completamente al azar (BCA), con diferentes distancias de siembra en las 6 parcelas con 20 repeticiones haciendo un total de 60 plantas para evaluar Tratamiento 1; Tratamiento 2; Tratamiento 3. Las variables evaluadas fueron: altura de la planta; emisión foliar; número de hojas; clorofila (tercera hoja); área foliar; fuste de la planta se colocó la misma fertilización en las diferentes distancias para ver el efecto. El análisis de los datos nos fue indicando que en su etapa vegetativa no hay significancia estadística sino numérica que no se ven influenciadas por la interacción de la distancia de siembra; los métodos de siembra no afectaron a las variables. Su emisión foliar en su fase vegetativa (1.2 hojas semanales) la distancia que mayor cambio estadístico fue Tratamiento 3 (1.3 hojas) con su media más alta comparando con las otras distancias; se obtuvo el mejor resultado al disminuir la distancia de siembra. En su altura el Tratamiento 1 con (46.34 cm) mientras que el mientras que el Tratamiento 3 alcanzo (46.27 cm) y Tratamiento 2 alcanzo sus medias (46.24 cm) respectivamente. Con respecto a las variables del número de hojas destaca el tratamiento 1 siendo el mejor resultado en hojas (12.50) mientras que el Tratamiento 2 alcanzo sus medias (12.43) y Tratamiento 3 (12.36); el fuste destaca el Tratamiento 1 fue el mejor resultado (2.03 cm); con respecto al área foliar el resultado que más destaca es el Tratamiento 1 con un resultado (0.27 〖cm〗^2); su variable clorofila se tomó la tercera hoja para ver el verdor de la hoja el mejor tratamiento en las diferentes distancias es Tratamiento 1 obtuvo el mejor en clorofila (62.01 µ.〖cm〗^(-2)). El tratamiento 1 en las siguientes variables tuvo el mejor resultado; (Altura) con un valor de 46.34, numero de hojas con un valor de 12.50 hojas, fuste con 2.03 cm, área foliar con un valor de 0.27 〖cm〗^2 y la clorofila con un valor de (62.01 µ.〖cm〗^(-2)). En el Tratamiento 1 las distancias de siembra no influyen en los primeros estadios en cuanto a las variables que comprobamos en el ensayo; también a la vista humana el cultivo no presentaba mayores diferencias en los lotes.
Keywords: BANANO; DISTANCIA; SIEMBRA; PRODUCTIVIDAD